Reinas y Madres: representaciones y roles maternos de las mujeres de la realeza portuguesa entre los siglos XIII y XV - Mariana Bonat Trevisan (E-Spania)
In this article we problematize the imaginary and representations regarding maternal roles and the performances of women who were mothers of heirs and occupied the position of queens of Portugal between the 13th and 15th Centuries. In a context crossed by two dynasties, we seek to analyze continuities and ruptures between the images built about these queens as mothers, their actions and relationships with their children, as well their political implications. Through different documentar records, we verified how much was valued, depreciated and used discursively and politically the maternal roles and performances of the sovereign Isabel of Aragon (1270-1336) – the holy queen, Beatriz of Castille (1293-1359), Leonor Teles (1350-1405), Filipa of Lancaster (1360-1415) and Leonor of Aragon (1405/1408-1445).